Optimizing Receiving Operations in the Hospitality Industry: A Case Study of Sensory Validation and Supplier Accountability at Hotel New Saphir Yogyakarta - Muhammad Aji Farhan Naja; Dessy Isfianadewi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The purpose of this study is to examine the strategies employed by Hotel New Saphir Yogyakarta in addressing operational challenges within the receiving process, specifically concerning quantitative discrepancies, delivery delays, and quality non-compliance. We adopted a qualitative single case study design, utilizing participant observation over a four-month period and semi-structured interviews with the Chief Accountant, Purchasing Officer, and Receiving Officer. We also analyzed internal documents such as Market Lists, Bin Cards, and invoices to verify procurement accuracy. Our findings reveal that the hotel successfully mitigates procurement risks through a combination of rigorous sensory validation protocols—such as olfactory and gustatory tests for perishable goods—and a graduated three-strike supplier warning system. We found that cross-departmental communication acts as a vital real-time feedback loop, ensuring that discrepancies in weight or quality are addressed through immediate negotiation rather than simple rejection. This research provides original value by highlighting the indispensable role of human sensory expertise as a qualitative filter that complements digital inventory metrics in high-standard hospitality environments. While limited to a single organizational context, the study offers practical implications for practitioners to institutionalize organoleptic standards and structured supplier discipline to safeguard operational integrity.